2015
DOI: 10.1140/epjc/s10052-015-3730-0
|View full text |Cite
|
Sign up to set email alerts
|

Generalized second law of thermodynamics for non-canonical scalar field model with corrected-entropy

Abstract: In this work, we have considered a non-canonical scalar field dark energy model in the framework of flat FRW background. It has also been assumed that the dark matter sector interacts with the non-canonical dark energy sector through some interaction term. Using the solutions for this interacting non-canonical scalar field dark energy model, we have investigated the validity of generalized second law (GSL) of thermodynamics in various scenarios using first law and area law of thermodynamics. For this purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Huang, et al [62] utilized scalar-tensor theory to prove that UFL is identical to Friedmann equations and also found that GSLT is valid for apparent horizon. Das, et al [63] investigated thermodynamics of universe and found that GSLT is valid on both apparent and event horizons under the realm of non-canonical scalar fields DE model. Khan, et al [41] utilized cubic gravity with Λ term to investigate the different cosmological parameters, GSLT and found that they lie in the ranges of observational bounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang, et al [62] utilized scalar-tensor theory to prove that UFL is identical to Friedmann equations and also found that GSLT is valid for apparent horizon. Das, et al [63] investigated thermodynamics of universe and found that GSLT is valid on both apparent and event horizons under the realm of non-canonical scalar fields DE model. Khan, et al [41] utilized cubic gravity with Λ term to investigate the different cosmological parameters, GSLT and found that they lie in the ranges of observational bounds.…”
Section: Introductionmentioning
confidence: 99%
“…Khan, et al [41] utilized cubic gravity with Λ term to investigate the different cosmological parameters, GSLT and found that they lie in the ranges of observational bounds. The above work especially [63] motivated us to investigate some cosmological parameters and the thermodynamic properties of universe in parameterized cubic gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in this model, a scalar field is minimally coupled to gravity to drive the accelerated expansion phase of the Universe. Indeed, various interesting possibilities with non-canonical scalar field has been recently studied in the literature for addressing several kinds of cosmological issues [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, the thermodynamical study of DE is a powerful apporoach for a better understanding of the unknown nature of the DE component (for details, see Refs. [12][13][14][15][16][17][18][19]) and thermodynamical aspects are important in this respect. Based on experimental evidences, thermodynamical laws are applicable to different macroscopic systems.…”
Section: Introductionmentioning
confidence: 99%